The main stages of the history of research of the western area of the Trypillian culture - Skakun, Natalya; Terekhina, Vera; Tsvek, Elena (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2014)
The history of archaeological research on the Trypillian sites in the western regions of Ukraine can be subdivided into four stages, each of which is marked by certain achievements. The first explorations resulted in the discovery of new archaeological objects, which gave rise to the discussion about the interpretation of constructions and functions of the settlements. The questions related to chronology, periodization, and excavation methodology were discussed as well. However, this activity was irregular and spontaneous, and the materials of many sites were scattered over different museums of Europe. The later stages of research gave very important data about the material and sacral components of the Trypillian culture, as well as its development, ways of adaptation to natural conditions, relative chronology of the sites, and their distribution. In the last years, the systematic excavations conducted at the reference site of Bodaki shed an important light on the economic basics of Trypillia. They also gave new materials for reconstructing the connections between the north-western and central areas of the culture, and its connections with the coeval farming-herding cultures of Europe.
Główne etapy historii badań zachodniego obszaru kultury trypolskiej
This work was supported by RFBR, project № 13–06–90402.
Keywords: Trypillian culture; Western Ukraine; the history of research